Structural and Optical Characterization of Pure and Lanthanum Substituted Nd1–xLaxAlO3 Prepared by Sol–Gel Method - Akash S. Padole; Vikash Singar; Payal Ratnawat; Ansh Dabkara; Dibya Prakash Kar; Nikita Jain; Minal Gupta; Archna Sagdeo; Pankaj R. Sagdeo (ChemistryOpen)
This work demonstrates the tuning of crystal‐field parameters of Nd rare Earth ion in NdAlO3 through lanthanum (La) substitution; for this purpose, this work has prepared the polycrystalline samples of pure and La‐substituted NdAlO3 using the sol–gel synthesis method. The purity of the phase of Nd1–xLaxAlO3 (x = 0, 0.1, 0.2, 0.3, 0.4, 0.5) samples has been confirmed via X‐ray diffraction measurements. This work found that with La substitution, the lattice parameters systematically increase. The values of lattice parameters “a” and “b” changed from 5.315 Å (x = 0) to 5.339 Å (x = 0.5). The lattice parameter “c” also increased from 12.926 to 13.025 Å in these samples. Additionally, the Nd/LaO bond length increased from 2.419 to 2.469 Å. The NdONd bond angle shifted from 169.7° to 171.4°, whereas the AlOAl bond angle varies from 165.5° to 167.8° and the value of the tolerance factor from 0.9640 to 0.9700, indicating improvement in the structural distortion. The crystal‐field transitions are investigated using optical absorption spectroscopy; this work found that La‐substitution leads to changes in the transition peak 4F9/2, which is shifted from 676.99 nm for sample (x = 0) to 675.44 nm for sample (x = 0.5).